INTERVENSI PEKERJA SOSIAL TERHADAP PERMASALAHAN PSIKOSOSIAL KLIEN KORBAN PERDAGANGAN ORANG (Studi Kasus Di Shelter Harapan – Roxy Jakarta Pusat) - Ogur, Maria Mathildis (Jurnal Insani, 2018)
Human trafficking is a kind of slavery in the modern time. Human being as an image of God is destroyed. Using qualitative method, the aim of this study is to find out the psychosocial problems of the clients as the victims of human trafficking and its result of the intervention. The research location was conducted at Harapan Roxy Shelter-Central Jakarta. The selection of informants was carried out purposively. With the technique of collecting observation data, in-depth interviews, documentation found the main problems experienced by the client are depression, trauma, stress, inability to see, insomnia, nightmares, anxiety, despair, anger, confusion, and loss of memory. The interventions carried out through assessment: create a case record on psychological problems assisted by psychologists and social workers. Social rehabilitation services are through a process of mental guidance, spiritual approach, physical exercises, gymnastics, recreation, giving skills and preparation for returning clients, termination and monitoring. Social worker’s intervention results include: the physical appearance of the clients (look cleaner and healthier), they are being diligent in working, regularly resting, actively follow any activities that motivate the clients to begin new life. Psychologically, the clients feel comfortable, happy, free from the burden, have freedom and dare to express themselves. Spiritually, there are changes in them including praying regularly and feeling close to God. The role of social workers in this intervention is as counselors, mediators, and motivators. The recommendation proposed from the results of this study are the following preventions: the socialization of human trafficking, providing basic education, giving proper skill courses and cooperating with various stakeholders.